2022
DOI: 10.1049/bsb2.12036
|View full text |Cite
|
Sign up to set email alerts
|

Natural polymer‐based adhesive hydrogel for biomedical applications

Abstract: Hydrogel is a polymer network system that can form a hydrophilic three‐dimensional network structure through different cross‐linking methods. In recent years, hydrogels have received considerable attention due to their good biocompatibility and biodegradability by introducing different cross‐linking mechanisms and functional components. Compared with synthetic hydrogels, natural polymer‐based hydrogels have low biotoxicity, high cell affinity, and great potential for biomedical fields; however, their mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 284 publications
0
9
0
Order By: Relevance
“…Hydrogels based on natural polymers such as alginate, starch, cellulose derivatives, chitosan, gelatin, collagen, hyaluronic acid, pectin, and so on show good degradability, biocompatibility, nontoxic degradation products, good flexibility similar to natural tissue, and have natural abundance, which endows them with widespread applications in medicinal fields, for instance, as drug carriers, wound dressing for wound healing, substrates for cell culture, cell delivery systems, scaffolds for tissue regeneration, and so on ( Figure 4 ) [ 15 , 16 ].…”
Section: Natural Polymers For Biomedical Usementioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogels based on natural polymers such as alginate, starch, cellulose derivatives, chitosan, gelatin, collagen, hyaluronic acid, pectin, and so on show good degradability, biocompatibility, nontoxic degradation products, good flexibility similar to natural tissue, and have natural abundance, which endows them with widespread applications in medicinal fields, for instance, as drug carriers, wound dressing for wound healing, substrates for cell culture, cell delivery systems, scaffolds for tissue regeneration, and so on ( Figure 4 ) [ 15 , 16 ].…”
Section: Natural Polymers For Biomedical Usementioning
confidence: 99%
“…Hydrogels based on natural polymers such as alginate, starch, cellulose derivatives, chitosan, gelatin, collagen, hyaluronic acid, pectin, and so on show good degradability, biocompatibility, nontoxic degradation products, good flexibility similar to natural tissue, and have natural abundance, which endows them with widespread applications in medicinal fields, for instance, as drug carriers, wound dressing for wound healing, substrates for cell culture, cell delivery systems, scaffolds for tissue regeneration, and so on (Figure 4) [15,16]. Hydrogels based on natural polymers have emerged as promising alternatives for the ECM in biomedical applications due to their unique integration of biodegradability, Hydrogels based on natural polymers have emerged as promising alternatives for the ECM in biomedical applications due to their unique integration of biodegradability, biocompatibility, mechanical property tunability, biomimicry, and responsiveness, which could provide microenvironments with the preservation of cellular functions, promotion of cell health, and encouragement of tissue formation [53].…”
Section: Hydrogel Preparation and Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Although the use of chitosan alone can be utilized to create hydrogels, the formed hydrogel may not have optimal gelling capacity to effectively carry the intended drug. [20][21][22] The solution lies in combining it with another polysaccharide polymer, alginate, which enhances the drug loading capacity in the hydrogel formulation. 23 Utilizing a multivalent cross-linker such as Ca 2+ , the gelation process in alginate forms a cross-linked framework that encapsulates the drug.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the research on hydrogels has shown an increasing trend, and their functions have become more and more abundant [ 26 , 27 , 28 ]. For example, Liu et al [ 29 ] and Fu et al [ 30 ] achieved high antimicrobial efficiency by loading antibacterial agents into hydrogels or by combining them with phototherapy.…”
Section: Introductionmentioning
confidence: 99%